Low-energy calibration of XENON1T with an internal 37 Ar source - Aprile, Elena; Lindner, Manfred; Marrodán Undagoitia, Teresa; Terliuk, Andrii (The European physical journal. C, Particles and fields, 2023)
A low-energy electronic recoil calibration of XENON1T, a dual-phase xenon time projection chamber, with an internal 37 Ar source was performed. This calibration source features a 35-day half-life and provides two monoenergetic lines at 2.82 keV and 0.27 keV. The photon yield and electron yield at 2.82 keV are measured to be (32.3 ± 0.3) photons/keV and (40.6 ± 0.5) electrons/keV, respectively, in agreement with other measurements and with NEST predictions. The electron yield at 0.27 keV is also measured and it is (68.0+6.3 −3.7 ) electrons/keV. The 37 Ar calibration confirms that the detector is well-understood in the energy region close to the detection threshold, with the 2.82 keV line reconstructed at (2.83 ± 0.02) keV, which further validates the model used to interpret the low-energy electronic recoil excess previously reported by XENON1T. The ability to efficiently remove argon with cryogenic distillation after the calibration proves that 37 Ar can be considered as a regular calibration source for multi-tonne xenon detectors.